Kontekstualisasi Hadis Hak Buruh Perspektif Hermeneutika Hassan Hanafi - Tri Mulyani; Hartati Hartati; Lukman Zain Muhamad Sakur (Jurnal Studi Hadis Nusantara, 2021)
This paper is based on a hadith phenomenon that occurs in the world of work. There is a lot of exploitation of labor rights or workers in it. Whereas in Islam (hadith) it is ordered to treat workers well as giving them their rights. The text of the hadith is understood textually and needs to be understood contextually so that the hadith can apply at all times, anytime and anywhere. To answer this, hadith must be studied with scientific integration, one of which is Hassan Hanafi's hermeneutics which includes 3 steps, namely: 1) historical criticism, 2) eidetic criticism, 3) practical criticism. written is to find out the contextualization of labor rights hadith in the perspective of Hassan Hanafi's hermeneutics. So that the need to seek law and contextualization of the hadith can be answered. The results of the study obtained an answer that the contextualization of the Prophet's hadith regarding labor rights does not only talk about wage rights. As experienced by the Prophet Muhammad when he became an employee of Sayyidah Khodijah. The text of the hadith which reads a'ṭū al-ajīro ajrohu (pay workers' wages) is understood contextually to be Hassan Hanafi's practical hermeneutics. Some rights with the aim of protecting and prospering workers include: The right to training opportunities, the right to a decent wage, the right to get wages on time, the right to rest, the right to social security, severance pay, the right to work, the right to association, the right to menstrual leave, pregnancy , giving birth, breastfeeding, the right to vacation, the right to worship, and the right to benefits. Keywords: Hadith, Wage Rights, Labor, Hassan Hanafi Hermeneutics